A tait-like equation for estimating the density of nontraditional super lightweight completion fluid at high pressure and temperature - Khalil, M.; Jan, B.M.; Abdul Raman, Abdul Aziz (Taylor & Francis Group, 2013)
Novel nontraditional super lightweight completion fluid (SLWCF) has been proven to be the best means to ensure the success of under balance perforation. Field test showed that the application of this new fluid has improved the well productivity. The authors present density measurements of SLWCF at high pressure and temperature. Density values of the fluid were measured in laboratory at high temperature ranging from 313.15 to 393.15 K, and pressure up to 25 MPa. Measured densities were fitted to a Tait-like equation. Calculated absolute average deviation, the maximum deviation, bias, and standard deviation values show that the developed model can be used to express the fluid density over a wide range of pressure and temperature. In addition, density value predicted by a Tait-like equation shows a good agreement both with laboratory and field data.